Impact of main sequence mass loss on the appearance, structure, and evolution of Wolf-Rayet stars - Josiek, Joris; Ekström, S.; Sander, Andreas A. C. (Astronomy and astrophysics, 2024)
Context. Stellar winds are one of the most important drivers of massive star evolution and are a vital source of chemical, mechanical, and radiative feedback on the galactic scale. Despite its significance, mass loss remains a major uncertainty in stellar evolution models. In particular, the interdependencies between the different approaches and the subsequent evolutionary stages and predicted observable phenomena are far from being systematically understood. Aims. In this study, we examine the impact of main sequence mass loss on the structure of massive stars throughout their entire evolution. Particular focus is placed on the consequences in terms of entrance into the Wolf-Rayet (WR) regime and the subsequent evolution. Methods. Using the Geneva stellar evolution code (GENEC), we computed grids of single, nonrotating stellar models at solar and Large Magellanic Cloud (LMC) metallicities of initial masses between 20 and 120 solar masses, with two representative prescriptions for high and low main sequence mass loss. Results. We obtain detailed numerical predictions regarding the structure and evolution of massive stars, and infer the role of main sequence mass loss by comparison of the mass-loss rate prescriptions. We present implications for the overall evolutionary trajectory, including the evolution of WR stars, as well as the effect on stellar yields and stellar populations. Conclusions. Mass loss during the main sequence plays an important role because of its ability to affect the sequence and duration of all subsequent phases. We identify several distinct evolutionary paths for massive stars, which are significantly influenced by the chosen main sequence mass-loss description. We also discuss the impact of uncertainties - other than that regarding mass loss - on the evolution, in particular those relating to convection. We further demonstrate that not only the total mass loss but also the specific mass-loss history throughout a star’s life is a crucial determinant of many aspects, such as the resulting stellar yields.